Living Harmoniously with the River Again: Case Study of the Urban Ecoriparian CSR Program by PT Pertamina Patra Niaga Aviation Fuel Terminal Halim Perdanakusuma - Tumansery, Andreas; Maulana, Wahyu; Sidiq, Ilham; Nofadila, Tefy; Sirait, Joshua Yoga Frans; Yunisha, Afifah Nur; Islami, Ivon Dewinda (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
In many places around the world, riparian areas of rivers serve as arenas for both livelihood and conflict among various stakeholders. This is also true for the riparian area of the Ciliwung River in Cawang Village, East Jakarta, Indonesia, which possesses unique social, ecological, and political dynamics that can serve as a reference for studies on riparian zones in urban settings. By focusing on the journey of the Urban Ecoriparian Program initiated and implemented by the Kelompok Tani Saung Cawang and the Kelompok Siaga Air Ciliwung in collaboration with the CSR team of PT Pertamina Patra Niaga AFT Halim Perdanakusuma, this qualitative study highlights flood disaster mitigation efforts that have been in place since 2021. The findings of this study reveal, firstly, that the flood issues in the Cawang riparian area are not merely environmental problems but are also deeply rooted in social and political issues. Secondly, these issues are being addressed through the Ecoriparian Program by adapting to the unique challenges and experiences of the Cawang community, which has developed an involutive adaptation pattern to floods. Thirdly, this program’s alignment with the community’s adaptation pattern has led to broader acceptance and active participation from the Cawang community. Fourthly, the program has spurred various transformations, including individual, collective, and even political changes, as it has influenced and resulted in flood management policies at the village level. Fifthly, the resulting village-level policies demonstrate that the program has also contributed to political education for the Cawang community.